Liberation /Summit - Agrawal, Nidhi (Ars Medica, 2024)
The author’s work draws inspiration from the distinct theories illustrated in religious texts such as Vedas and Puranas. She has worked on the concept of Ardhanarishwar, psychological disorders, and her pieces are coordinated with different subjects. Subsequently, she writes as she talks to God!